Numerical analysis of stress singularities at the apex of a cone with unsmooth lateral surface - Korepanova, Tatyana Olegovna; Matveenko, Valery Pavlovich; Sevodina, Natalya Vital'evna (Computational Continuum Mechanics, 2010)
We consider two variants of construction of the eigensolutions of the linear theory of elasticity for a semi-infinite cone having generatrices on its lateral surface, where the surface smoothness is broken or where the boundary conditions are changed. This study presents numerical results concerning stress singularity indices at the apex of a circular cone with mixed boundary conditions on its lateral surface and for a cone with unsmooth lateral surface.
Keywords: stress singularity; conic bodies; finite-element method